2022
DOI: 10.1002/nop2.1509
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of self‐directed learning ability, self‐efficacy and academic burnout of junior nursing college students in closed management colleges

Abstract: Aims To understand the status quo of self‐directed learning ability, self‐efficacy and academic burnout of junior nursing college students, since the closed management mode was implemented during COVID‐19 pandemic disease. Design Cross‐sectional study. Methods Participants came from 3,051 junior nursing college students of a college in Zhengzhou City, Henan Province, China. Data were collected by online questionnaire and analysed by SPSS25.0 (a statistical package for social science) and AMOS24.0 software. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…This study found nursing students with a moderate level of SDL ability, supported by previous studies [ 30 , 31 ]. In line with a previous study [ 18 ], our study confirmed the negative relationship between SDL ability and burnout, indicating the active role of SDL ability in reducing nursing students' burnout. In the stressful learning environment, SDL ability could foster students' problem-solving ability and help them effectively cope with academic difficulties [ 19 ], which may be beneficial for alleviating students’ stress.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study found nursing students with a moderate level of SDL ability, supported by previous studies [ 30 , 31 ]. In line with a previous study [ 18 ], our study confirmed the negative relationship between SDL ability and burnout, indicating the active role of SDL ability in reducing nursing students' burnout. In the stressful learning environment, SDL ability could foster students' problem-solving ability and help them effectively cope with academic difficulties [ 19 ], which may be beneficial for alleviating students’ stress.…”
Section: Discussionsupporting
confidence: 92%
“…Higher SDL ability can facilitate the acquisition of professional knowledge and skills and enable students to become lifelong learners [ 16 ]. Higher SDL ability was also associated with lower burnout and better problem-solving ability and academic performance among nursing students [ [17] , [18] , [19] ]. As an effective learning ability, SDL ability may help students improve their learning effects and alleviate their academic stress.…”
Section: Introductionmentioning
confidence: 99%
“…Self-directed learning involves establishing learning objectives and plans and adopting cognitive, motivational, and behavioral strategies effectively, which is essential for successful learning by immersing oneself in learning ( 38 , 39 ). Meanwhile, self-directed learning competency is an important determinant of academic achievement ( 40 ) and is associated with low academic burnout ( 41 ). It has a mediating effect on the relationships between various variables, such as emotional intelligence and creative performance ( 42 ), nursing students’ caring and resilience ( 43 ), learning motivation and learning flow ( 44 ), growth mindset and perceived academic achievement ( 45 ), and undergraduates’ level of career decisions and learning satisfaction ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, students’ normal learning and clinical practice are interrupted, and online learning lacks an effective supervision mechanism, which will affect students’ learning consciousness and academic self-efficacy. Students are vulnerable to external interference, which reduces learning efficiency, enthusiasm, confidence and academic self-efficacy [ 9 ]. Nearly half of the students reported different levels of anxiety (46.6%) and generally did not meet the clinical diagnostic criteria for anxiety (4.60 ± 4.271).…”
Section: Discussionmentioning
confidence: 99%
“…These academic pressures require them to have a high level of academic self-efficacy to complete their learning tasks and goals. However, the COVID-19 pandemic has reduced the academic self-efficacy of college students, and junior nursing college students reported that their academic self-efficacy was only at a moderate level [ 9 , 10 ]. Low academic self-efficacy will lead to the weakening of students’ learning motivation, learning ability and learning effect, thus hindering their reserve of professional knowledge and increasing the sense of uncertainty in clinical work [ 4 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%